Prediction of complications in the postoperative period in patients with multiple traumas of the gastrointestinal tract (Eurasian Research Bulletin, 2022)
The paper presents the developed methods for the early diagnosis of complications in the postoperative period in 180 patients with multiple trauma of the gastrointestinal tract, who were treated in the Department of Emergency Abdominal Surgery of the Fergana branch of the Republican Scientific Center for Medical Emergencies